Proceedings of ELM-2014 - Cao, Jiuwen; Mao, Kezhi Mao; Cambria, Erik; Man, Zhihong; Toh, Kar-Ann (Springer, 2015)
This book contains some selected papers from the International Conference on Extreme Learning Machine 2014, which was held in Singapore, December 8-10, 2014. This conference brought together the researchers and practitioners of Extreme Learning Machine (ELM) from a variety of fields to promote research and development of "learning without iterative tuning". The book covers theories, algorithms and applications of ELM. It gives the readers a glance of the most recent advances of ELM.